Determinasi Motivasi Kerja, Budaya Organisasi dan Gaya Kepemimpinan terhadap Kinerja Pegawai - Surya Akbar; Riza Efendi (STIA Indragiri, 2017)
ABSTRACTImproving performance is not easy because of many factors that affect a person's high and low performance. Employee performance is one thing that is very important in an organization to achieve objectives so that organization should do to improve it. The purpose of this research was for analyze the determination of motivation, organizational culture and leadership style against performance in Bengkong District Office partialy and simultaneously. The population in this study are the Bengkong District Office Employee totaling 57 peoples, using the Slovin formula, a sample is taken to represent the study population and the result to represent the population are 50 peoples. Sampling and population was randomly so that each employee has an equal opportunity to be selected as a sample.The research approach used in this study is a quantitative approach, while the kind of research is a survey while the descriptive analytic method by means of data analysis using multiple linear regression. The data collection by questionnaire and analyzed by regression using SPSS version 22.The results of the data analysis of the data obtained regression coefficient of work motivation (b1) = 0241 with Sig. 0.148. The regression coefficient Cultural Organization (b2) = 0.096 with Sig. 0.410. Leadership Style regression coefficient (b3) = 0.291 with Sig. 0.824. Then the F value is 2.557 with the Sig. 0,067.Results showed that motivation, organizational culture and leadership style determiner against performance in Bengkong District Office. Keywords : Work Motivation, Organizational Culture, Leadership Style, Performance.